Sifat Fisik Vermikompos Feses Sapi Dengan Penambahan Limbah Sayur Kol (Brassica Oleracea Var. Capitata) - Ardhani, Yamin; Syarifuddin, Hutwan; Novianti, Sri (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aimed to determine the effect of adding cabbage waste (Brassica oleracea var. capitata) to cow feces in vermicomposting using African Night Crawler worms (Eudrilus eugeniae). The study was conducted in the Animal and Forage Cultivation Laboratory, Faculty of Animal Husbandry, University of Jambi, for one month, using a Completely Randomized Design (CRD) with four treatments and five replications. The treatments consisted of varying amounts of vegetable waste: V1 (200 g), V2 (250 g), V3 (300 g), and V4 (350 g), each mixed with 300 g of cow feces and 25 g of ANC worms. The vermicomposting process indicated compost maturity with a blackish color, an earthy odor, and a smooth texture. The addition of 250 g of cabbage waste (V2) produced the best physical characteristics. The temperature ranged from 29–32°C and humidity 44–66%, while the water content was 44–65%, with the final value approaching the Indonesian National Standard (SNI) (≤50%). The analysis results showed no significant differences between treatments (p>0.05), suggesting that parameter changes were more influenced by the decomposition stage and duration of the composting process. Differences in the number of cabbages did not significantly affect the physical properties of the vermicompost.